Two new species and one new record of the genus Caliscelis de Laporte (Hemiptera: Fulgoroidea: Caliscelidae) from China - Che, Yanli; Wang, Yinglun; Zhang, Yanlin (Zootaxa, 2011)
This paper examines five species of the genus Caliscelis de Laporte, of which two new species, C. rhabdocladis sp. nov.and C. triplicata sp. nov., are described and illustrated, C. affinis Fieber is reported for the first time from China, and other two known species C. orientalis Ôuchi and C. chinensis Melichar are redescribed and illustrated. A checklist of the world Caliscelis fauna and a key to all Chinese species of Caliscelis are provided.